Stool Microbiome Features and Weight Change Response to Treatment for cancer cachexia - Rima Nasrah; Mary Kanbalian; Christina Van Der Borch; Ken Dewar; Stéphanie Chevalier; R. Thomas Jagoe (Journal of Cachexia, Sarcopenia and Muscle, 2025)
ABSTRACT Background and Aims Cancer cachexia is characterised by significant weight loss and muscle wasting that adversely affects patient outcomes. Nutritional interventions in cancer cachexia leads to improved outcomes, including improved weight change. However, there are wide variations in weight response to dietary interventions. Thus, it remains difficult to predict response to a given increase in dietary intake at an individual patient level. This study aimed to identify gut microbiome features that could serve as potential predictive biomarkers for response to individualized dietary intervention in patients with cancer cachexia attending the McGill Cancer Nutrition‐Rehabilitation Program at the Jewish General Hospital (CNR‐JGH). Methods Participants were recruited from CNR‐JGH clinic. Interventions included individualized nutritional counselling by a registered dietitian, to increase energy and protein intake to meet recommended levels. Stool DNA samples were collected at baseline (V1) and visit 2 (V2), and gut microbiome profiles were analysed to assess microbial diversity and identify differentially abundant genera in patients who lost weight (WL, N = 8) vs. maintained/gained weight (WSG, N = 29) at subsequent CNR‐JGH clinic visits. Results Greater alpha‐diversity and higher Lachnospira genus abundance at baseline predicted higher likelihood that patients would have good response to CNR‐JGH intervention (WSG at V2). Though predictors of poor response to nutritional intervention (WL at V2) were not identified, subjects in the WL group exhibited lower alpha‐diversity and greater microbial population instability after CNR‐JGH interventions. Conclusions In this cohort of patients with cancer‐related weight loss attending a cancer cachexia clinic, certain gut microbiome features were associated with response to dietary interventions. Patients who lost weight after CNR‐JGH intervention also developed a less diverse and less stable gut microbiome. Lachnospira genus abundance is a potential predictor of positive weight change response to dietary intervention as part of multimodal care for cancer cachexia, and further confirmatory studies are warranted. In addition, targeted dietary approaches to maintain diversity and gut microbiome population stability may have a role in improving the response to dietary interventions in cancer cachexia.